Educators as agents of breadth-biased learning: using social reconstructionism as rationale for embracing media multitasking and enhancing teaching practices in higher education - Kassie, Seada A. (Frontiers in Psychology, 2024)
This perspective article contends that media multitasking has significant implications on cognitive control processes, particularly in how information is processed and utilized. Contrary to viewing media multitasking as inherently negative, the article argues that it contributes to the evolving nature of cognitive processing, without necessarily improving or degrading it. The discussion draws on theoretical frameworks from contemporary cognitive neuroscience to contextualize these arguments. The article provides a nuanced perspective on media multitasking, acknowledging its enduring presence and exploring its influence on cognitive processes, while also proposing strategies for educators to navigate its implications in educational settings.